Digital restoration of fragmentary human skeletal remains: Testing the feasibility of virtual reality - Jurda, Mikoláš; Urbanová, Petra; Chmelík, Jiří (Journal of forensic and legal medicine, 2019)
Experts in forensic anthropology and medicine have become gradually accustomed to examining components of the human body in the virtual workspace. While the computer-assisted approach offers numerous benefits, the interactions with digital three-dimensional biological objects are often problematic, particularly if conducted with mouse, keyboard and flat-panel screen. The study focusses on feasibility of a virtual reality (VR) system for virtual restoration of fragmentary skeletal remains. The VR system was confronted with three cases of fragmentary remains. The cases were reassembled manually by twenty participants using a HTC Vive headset combined with an in-house application A.R.T. The same task was performed using a CloudCompare software in conjunction with a desktop peripheral. The two systems were compared in terms of time efficiency, the geometric properties of the resulting restorations, and convenience of use. Restoration using the VR system took approximately half the time the desktop set-up did. The VR system also yielded a lower error rate when a severely fragmented skull was reassembled. Ultimately, although the efficiency of the reassembling was shown to be strongly dependent on the operator's experience, the use of the VR system balanced out the uneven levels of proficiency in computer graphics. The current generation of virtual reality headsets has a strong potential to facilitate and improve tasks relating to the virtual restoration of fragmented skeletal remains. A VR system offers an intuitive digital working environment which is less affected by an operator's computer skills and practical understanding of the technology than the desktop systems are.
Keywords: Fragmentation; Body Remains; Imaging, Three-Dimensional; studie proveditelnosti; Virtual reality; Humans; lidé; Software; fraktury lebky; Wounds, Gunshot; tělesné pozůstatky; počítačové zpracování obrazu; Female; Male; Image Processing, Computer-Assisted; Adult; zobrazování trojrozměrné; software; Virtual Reality; Feasibility Studies; Skull Fractures; mužské pohlaví; Skeletal injuries; ženské pohlaví; virtuální realita; Reassembly; dospělí; Virtual approach; střelné rány; soudní antropologie; Forensic Anthropology